Dairy product consumption and calcified atherosclerotic plaques in the coronary arteries: The NHLBI Family Heart Study. (June 2022) - Neisius, Ulf; Zhou, Guohai; Ward, Rachel E.; Ellison, R. Curtis; Gaziano, J. Michael; Djoussé, Luc
Summary: Background & aims: Diet modification is a major component of non-pharmacological coronary heart disease (CHD) prevention. Few studies have examined the association between consumption of different dairy products with subclinical coronary artery disease. We sought to examine whether milk, yogurt, or cheese consumption is associated with calcified atherosclerotic plaques in the coronary arteries. Methods: We cross-sectionally examined 2278 participants from the National Heart, Lung, and Blood Institute Family Heart Study. Dairy consumption was assessed by a semiquantitative food frequency questionnaire. Coronary artery calcium (CAC) was estimated by cardiac computed tomography. We used an Agatston score of ≥100 to indicate prevalent CAC and fitted multivariable logistic regression to calculate adjusted odds ratios. Results: Mean age was 58 ± 13 years and 45% were male. The frequency of milk (≤1/week, 2–4/week, and ≥5/week; 22%, 14%, and 64%, respectively), yogurt (almost never, <1/week, and ≥1/week; 54%, 20%, and 26%, respectively), and cheese consumption (<1/week, 1/week, 2–4/week, and ≥5/week; 15%, 17%, 41%, and 27%, respectively) varied in the cohort. We observed an inverse association of cheese consumption with prevalent CAC: odds ratio (95% CI) of 0.63 (0.42–0.94) when comparing cheese intake of ≥5 servings/week with <1/week, adjusting for sex, age, body mass index, cigarette pack years, presence of CHD, family income, and education (p for linear trend 0.007). In contrast, there was no association between yogurt or milk consumption and CAC (p for linear trend 0.51 and 0.87, respectively). Conclusion: Our data suggest that cheese consumption but not yogurt or milk is associated with a lower odds of CAC in men and women.